The car parking simulator / Hong Lai Chin - Hong , Lai Chin (2005)
As a fulfillment to our Computer Science Degree Program in University of Malaya, all undergraduates students are required to accomplish a final year project (thesis) which is divided into 2 parts; there are thesis I and thesis II. In this semester, all undergraduate need to finish their thesis part I follow by thesis part II. The purpose or final year project is to let the undergraduate to put all theoretical knowledge learnt in past two years into practical before going to work. It is also as a scale to measure how much they learnt and put into practice. I have taken project titled “The Car Parking Simulator” as my final year project. It is a web-based application which allows the respective user to simulate car parking in a realistic environment in Malaysia. The objective or this simulator to improve the parking skill among road user and familiarize them with parking environment with minimum damage and maximum impact. This simulator will cover every type of car parking available in Malaysia which includes side parking, parallel parking and slanting parking. Unified process, an object-oriented methodology has been chosen as the development process. The application will develop by using Avtive Server Pages. (ASP) JavaScript is use as a client side scripting language and VBScript as server side scripting language. Macromedia Flash MX will also be used too for interactive and animation. By using this application, user can simulate car parking, view information on car parking, views simulation result and generate report.